Utility Maximization Based on Cross-Layer Design for Multi-Service in Macro-Femto Heterogeneous Networks - Zhang, Xiuning; Tan, Zhenhui; Xu, Shaoyi; Tao, Cheng (IEEE transactions on wireless communications, 2013)
We have developed a new cross-layer scheme, which can efficiently characterize the interactions across five layers. The optimization problem is formulated, so as to maximize the weighted sum utility, subject to constraints coupling different layers. We give a mathematical characterization of these layers and formulate a mixed integer nonlinear program (MINLP) problem. The optimization problem is non-deterministic polynomial-time hard (NP-hard). In this paper, we propose a greedy-based heuristics algorithm. Simulation results show that the proposed heuristic scheme can achieve system throughput very close to the upper bound of the optimal solution in the moderate-scale network, and higher than those of the simple cross-layer design (SCLD) scheme and the no CLD scheme in the large-scale network.